Cooperation Frameworks of Indonesia and Cambodia Against Transnational Organized Crime in Online Gambling Human Trafficking - Valerisella, Nila; Sliviani, Ninne Zahara; Situmeang, Ampuan (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2025)
Trafficking in Person (TIP) is a transnational crime affecting both countries of origin and destination, with significant implications for vulnerable individuals, particularly those in the online gambling sector. This research explores the categorization of TIP victims working abroad, focusing on legal frameworks and government cooperation to combat this issue. Using a normative juridical approach and qualitative analysis, the study emphasizes the urgency of cross-border collaboration in TIP prevention. The findings highlight the critical need for strengthened international agreements, regional cooperation, and the enforcement of robust legal sanctions against transnational crime syndicates. This research contributes to a deeper understanding of TIP within specific sectors and proposes actionable recommendations to enhance global anti-trafficking efforts.